Pengaruh Gaya Kepemimpinan dan Motivasi Kerja terhadap Kinerja Karyawan dengan Komitmen Organisasi sebagai Variabel Intervening pada Badan Pengelolaan Keuangan dan Aset Daerah Provinsi Sumatera Barat - Azzahra Andrescha; Marta Widian Sari; Ai Elis Karlinda (Jurnal Transformasi Bisnis Digital, 2026)
This study aims to analyze the influence of leadership style and work motivation on employee performance with organizational commitment as an intervening variable at the Regional Financial and Asset Management Agency of West Sumatra Province. This study uses a quantitative approach with an explanatory design. Data were collected through distributing questionnaires to 45 employees using a census technique. Data analysis was conducted using Structural Equation Modeling (SEM) with the Partial Least Square (PLS) approach. The results show that leadership style and work motivation have a positive and significant effect on organizational commitment. In addition, leadership style and work motivation also have a positive and significant effect on employee performance. However, organizational commitment does not have a significant effect on employee performance and is unable to mediate the influence of leadership style and work motivation on employee performance. These findings indicate that improving employee performance in public sector organizations is more effective through directly strengthening leadership style and work motivation. This study is expected to provide theoretical contributions in the development of public sector human resource management studies and become practical considerations for organizational leaders in formulating human resource management policies oriented towards improving apparatus performance.